2007
DOI: 10.1063/1.2508701
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Really Influence Shifts in Students’ Attitudes and Expectations in an Introductory Physics Course?

Abstract: To gauge the impact of instruction on students' general expectations about physics and their attitudes about problem solving, we administered two different, but related, survey instruments to students in the first semester of introductory, calculus-based physics at McDaniel College. The surveys we used were the Maryland Physics Expectation Survey (MPEX) and the Attitudes about Problem Solving Survey (APSS). We found that the McDaniel College students' overall responses were more "expert-like" post-instruction:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The adapted AAPS instrument was prepared by Mason and Singh (2010) based on the Maryland Physics Expectation Survey (Redish et al, 1998), as developed by Marx and Cummings (2007) and Cummings, Lockwood, and Marx (2004) with the purpose of identifying students' epistemological beliefs towards learning physics for the first time. Its validity has already been verified, having been implemented for many beginner and advanced physics students in the United States.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…The adapted AAPS instrument was prepared by Mason and Singh (2010) based on the Maryland Physics Expectation Survey (Redish et al, 1998), as developed by Marx and Cummings (2007) and Cummings, Lockwood, and Marx (2004) with the purpose of identifying students' epistemological beliefs towards learning physics for the first time. Its validity has already been verified, having been implemented for many beginner and advanced physics students in the United States.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Since research has found relationships between students' beliefs and their performance on the course, studies have focused on this area during the last decade. Except for several studies which have reported gains on the MPEX (e.g., Elby, 2001;Marx and Cummings, 2007), studies in this area generally reported deteriorating post MPEX scores (e.g., Redish et al, 1998;Ornek, Robinson, and Haugan, 2008 Aforementioned studies emphasize the importance of expectations in how students make sense of their world and their learning. If inappropriate expectations play a role in students' common difficulties with introductory calculus-based physics, they need to be tracked and documented in order to help students improve their expectations which may in turn increase their success and enrollment in introductory physics classes.…”
Section: Expectations About Physicsmentioning
confidence: 99%
“…Furthermore, when introductory students were asked to answer CLASS survey questions from their own and their professors' perspectives, they seemed to be able to respond in a more expertlike manner when considering their professors' point of view, but maintained a less expertlike stance when answering from their own point of view [6]. These trends in student epistemology towards physics and learning physics are difficult to overcome, and relatively few, carefully designed introductory physics courses and curricula are able to produce a positive change in these attitudes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cummings et al [14,17] developed the Attitudes toward Problem Solving Survey (APSS) from the MPEX survey in order to focus specifically on students' attitudes toward physics problem solving [17]. When administered in introductory physics classrooms in three different institution types, the APSS results showed that students' attitudes about problem solving did not improve after instruction, and that attitudes were least expertlike (least favorable) at the large university with a large class size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation